PENERAPAN AJARAN MELAWAN HUKUM TERHADAP TINDAK PIDANA KORUPSI: STUDI TERHADAP TINDAK PIDANA KORUPSI YANG DIPUTUS SETELAH PUTUSAN MAHKAMAH KONSTITUSI NOMOR 003/PUU-IV/2006 - Azrijal, Azrijal (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
The purpose of this study is to analyze the application of the teachings against the law against acts of corruption that violate the provisions of Article 2 of Law No. 31 of 1999 Jo Law Number 20 of 2001 after the Constitutional Court Decision Number 003 / PUU-IV / 2006 and criminal prosecution of perpetrators criminal acts of corruption that violate the provisions of Article 2 of Law Number 31 of 1999 Jo Law Number 20 of 2001 after the decision of the Constitutional Court Number 003 / PUU-IV / 2006. The teachings against the law that are regulated in the provisions of Article 2ayat (1) of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 include teachings against the law in formal and material terms. However, after the Constitutional Court's Decision Number 003-PUU / IV / 2006 stated that it was against the law recognized in the provisions of Article 2 paragraph (1) of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 as long as it was against formal law. This means that as the final and binding nature of the Constitutional Court's decision, after the Constitutional Court's decision a criminal act of corruption that violates the provisions of Article 2 paragraph (1) in matters against the law must be interpreted as against the law in the formal sense and no longer permitted to interpret against the law in the material sense.